Global Exponential Stability of Discrete-Time Multidirectional Associative Memory Neural Network with Variable Delays. (16th October 2012) - Wang, Min; Zhou, Tiejun; Zhang, Xiaolan
Abstract : A discrete-time multidirectional associative memory neural networks model with varying time delays is formulated by employing the semidiscretization method. A sufficient condition for the existence of an equilibrium point is given. By calculating difference and using inequality technique, a sufficient condition for the global exponential stability of the equilibrium point is obtained. The results are helpful to design global exponentially stable multidirectional associative memory neural networks. An example is given to illustrate the effectiveness of the results.